(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to analyze the impact of Raw Resources within the framework of a rentier economy on the local economy, through a case study of iron ore in Wadi Al-Shati, Libya. The study adopts an applied analytical field approach, where data were collected using questionnaires and interviews with stakeholders in the mining sector and local municipalities in Wadi Al-Shati. The results, based on linear regression models, reveal a statistically significant inverse relationship between reliance on iron ore revenues as a rent-based income source and indicators of local development, such as indirect employment and economic diversification. This finding highlights the persistence of rentier patterns and the absence of effective resource utilization in the presence of weak institutional reforms.